Effect of grass-legume strip cropping and fertility levels on yield and quality of fodder in silvipastoral system under hot arid condition - Patidar, M; Mathur, B K; Rajora, M P; Mathur, D (The Indian Journal of Agricultural Sciences, 2008)
A study was undertaken at Jodhpur during rainy (kharif) season of 2003 and 2004 to assess the production potential of Cenchrus ciliaris L./Lasiurus sindicus Henr. and cowpea [Vigna unguiculata (L.) Walp.] sown in strips in association with early stage Colophospermum mopane Kirk ex Benth. and Hardwickia binata Roxb. stands with and without fertilizer application. The results showed that plant growth and survival percentage of C. mopane was higher than H. binata. The growth of C. mopane plants was affected by different strip cropping and fertilizer. Green and dry forage yields were influenced by the cropping systems and these were maximum with L. sindicus + cowpea system (8.99 and 3.08 tonnes/ha green and dry forage yield), followed by sole strip of L. sindicus (8.88 and 3.08 tonnes/ha green and dry forage yield) and C. ciliaris + cowpea cropping system (8.46 and 2.78 tonnes/ha green and dry forage yield) in kharif 2003. However, forage yield was recorded maximum in sole strip of C. ciliaris, followed by C. ciliaris + cowpea cropping system in kharif 2004. The mean data of two years revealed that green and dry fodder yields under different strip cropping were at par but protein yield was higher with L. sindicus + cowpea and C. ciliaris + cowpea system as compared to sole strip of C. ciliaris/L. sindicus. Application of 40 kg N/ha increased green and dry fodder yields by 10-12% over the control. Crude protein yield of grasses was also increased (61%) with inclusion of cowpea and fertilizer application. Water-use efficiency of grasses and cowpea was increased with nitrogen application.